Customer’s brand loyalty on sportswear: a case study of Adidas - Shafee, Nur Baiti; Fern, Yeo Sook; Suhaimi, Shadia; Hashim, Haniza; Hao, Gan Wei (International Journal of Psychosocial Rehabilitation, 2020)
Adidas sports dress has increased year by year growth to outwit other competitors and it is a challenge for sports dress brands to make the customers loyal to their product. Recently, the Adidas has always innovated and extending their brand’s functionality and purpose, these have made them more popular and lucrative that the brands are not just for a better performance for sport alone, but also to make clothes and foot wears to be used everyday. This study use questionnaire to evaluate loyalty customer on Adidas brand. Data gathered from questionnaire were analyzed using “Statistical Package for Social Science (SPSS)” to determine the correlation among the variables. Brand name show a significant relationship with customer loyalty Adidas sport attire. Research conclude that company have a good brand name will attract customer more easily, from the result of findings on this research as well as the good brand name can be present a reputation of the company. This study also shown a significant association between price and product quality towards customer loyalty on sport attire of the Adidas.